Exploring The Level Of Awareness For Integrated Teacher Education Programme In Young Pupil Teachers (Journal of Pharmaceutical Negative Results, 2023)
National Council of Teacher Education (NCTE) has recently introduced Integrated Teacher Education Programme (ITEP) for teacher education. NCTE has clearly stated the norms for ITEP and the institutes for teacher education are expected to match them strictly. Hence, it has become necessary to explore the awareness for ITEP in pupil teachers, Secondly, these pupil teachers are future teachers. Young pupil teachers are supposed to own a good level of awareness especially, in the field they have chosen as their career. They all were in the age group of 20-30 years. The researchers have developed an awareness scale. 75 females and 50 male young pupil teachers participated in the study. The data was analysed on MS Excel. A z-test was applied on the samples to test the hypotheses. There was a significant difference in the means of the two groups. Most of the pupil teachers scored in the medium level of awareness for ITEP. Suggestions are given to improve the awareness level for ITEP.